POLYMORPHISM OF INTER-SIMPLE SEQUENCE REPEATS (ISSR) IN ALLIUM SPECIES - A.S. Domblides; E.A. Domblides; L.U. Kan; V.S. Romanov (Овощи России)
Some onion species such as A. altaicum, A. odorum, A. fistulosum, A. nutans, A. schoenoprasum, A. altissimum, A.proliferum, A. tuberosum, A. subhirsutum, A.roylei, A.auctum, A.rupestre, A.vavilovii were taken to compare each other applying ISSR markers. Additionally to those interspecific onion hybrids A.cepa x A.nutans and А.сера x A. fistulosum were also analyzed. 5 ISSR primers were selected out of 15 ones tested. 76 % of polymorphic bands were found out. Hybrid progenies of crossing between A. nutans and A.cepa species were in dendrogram a slight closer to A. cepa group, whereas A. nutans was at the similarity with index 0.52 for A.cepa group and 0.49 for hybrid progenies. As it was confirmed the A. fistulosum and A. altaicum were genetically similar. The genetic similarity was also confirmed between A.altissimum and А.schoenoprasum that corresponded to the previous phylogenetic studies.